The predominant roles of the sequence periodicity in the self‐assembly of collagen‐mimetic mini‐fibrils - Chen, Fangfang (Protein Sci, 2019)
Collagen fibrils represent a unique case of protein folding and self‐association. We have recently successfully developed triple‐helical peptides that can further self‐assemble into collagen‐mimetic mini‐fibrils. The 35 nm axially repeating structure of the mini‐fibrils, which is designated the d‐period, is highly reminiscent of the well‐known 67 nm D‐period of native collagens when examined using TEM and atomic force spectroscopy. We postulate that it is the pseudo‐identical repeating sequence units in the primary structure of the designed peptides that give rise to the d‐period of the quaternary structure of the mini‐fibrils. In this work, we characterize the self‐assembly of two additional designed peptides: peptide Col877 and peptide Col108rr. The triple‐helix domain of Col877 consists of three pseudo‐identical amino acid sequence units arranged in tandem, whereas that of Col108rr consists of three sequence units identical in amino acid composition but different in sequence. Both peptides form stable collagen triple helices, but only triple helices Col877 self‐associate laterally under fibril forming conditions to form mini‐fibrils having the predicted d‐period. The Co108rr triple helices, however, only form nonspecific aggregates having no identifiable structural features. These results further accentuate the critical involvement of the repeating sequence units in the self‐assembly of collagen mini‐fibrils; the actual amino acid sequence of each unit has only secondary effects. Collagen is essential for tissue development and function. This novel approach to creating collagen‐mimetic fibrils can potentially impact fundamental research and have a wide range of biomedical and industrial applications.